ANALISIS PENGELOLAAN WAKAF PRODUKTIF MENURUT UNDANG UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF - Suid; Abdur Rahim (Jurnal Penelitian Multidisiplin Ilmu, 2022)
Waqf as one of the religious institutions that is closely related to socio-economic, the tendency of waqf is still managed in a conventional way. Where the waqf assets are still mostly used for places of worship. For this reason, an understanding of the function of waqf needs to be socialized and become a collective movement for all people in order to improve the people's economy. Regarding the issue of waqf, the government seriously issued Law Number 41 of 2004 concerning Waqf as a momentum to realize waqf productively. The purpose of this study is to find out the results of the analysis of productive waqf management according to Law Number 41 of 2004, and to find out the factors that become obstacles in the management of productive waqf according to Law Number 41 of 2004. This research is a type of library research. research, where the data sources are obtained from literature searches such as journal articles, internet sites, books, legal materials (laws), as well as other research results that are relevant to the topic of this research. The results of the analysis of productive waqf management according to Law Number 41 of 2004 is that in the management of productive waqf a strategy is needed, including the formation of an Indonesian waqf agency tasked with managing waqf funds and operating nationally, forming business partnerships to support the development of productive aspects of cash waqf funds. Meanwhile, the factors that become obstacles in the management of productive waqf according to Law Number 41 of 2004 are the lack of public understanding of waqf law, management and management of waqf which is still not good, waqf objects are generally land so it is difficult to develop, and the lack of ability of the waqf. nazhir (waqf manager) in managing waqf.